2023
DOI: 10.1037/mac0000104
|View full text |Cite
|
Sign up to set email alerts
|

Identity, narrative, and cultural–historical context in evaluating personal and public events.

Abstract: In this commentary, we suggest that a model explaining the dissociation between the evaluation of personal and public past and future events proposed by Liu and Szpunar (2023) might profit from considering more systematically the cultural-historical context of selecting and evaluating events. This would entail identifying psychological mechanisms which, in combination with contextual variation, predict the proposed dissociation or other evaluative configurations. We suggest combining self-enhancement with inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…For instance, Zerr et al (2023) suggest that the valence-based dissociation between personal and collective cognition may be tied to the fluency-based cueing techniques that have dominated early studies in this area. Moreover, Zerr et al (2023) and Habermas et al (2023) suggest that additional work with narrative-based techniques is needed to better understand not just what events come to mind but the situational context, meaning, and function of those events (see also Daley et al, 2023; Hirst & Topçu, 2023).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, Zerr et al (2023) suggest that the valence-based dissociation between personal and collective cognition may be tied to the fluency-based cueing techniques that have dominated early studies in this area. Moreover, Zerr et al (2023) and Habermas et al (2023) suggest that additional work with narrative-based techniques is needed to better understand not just what events come to mind but the situational context, meaning, and function of those events (see also Daley et al, 2023; Hirst & Topçu, 2023).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Choi and Liu (2023) used such a method with an American sample and found that approximately 65% of the sample was able to provide an overall historical narrative. The fact that about a third of a small but stratified American sample was unable to provide a meaningful account of their historical event nominations suggests some possible limitations to Zerr et al (2023) and Habermas et al’s (2023) call for the use of more narrative-based techniques. Nonetheless, the detail (or lack thereof) with which people are able to contextualize their nationally oriented cognitions should help to further illuminate our understanding of collective cognition.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations